Integrated sustainability of civil society organizations in Ecuador: between survival and extinction (2018)
This article addresses the importance of rejecting the idea according to which every efficient institution is a consistent result of a centralized political power intentionality. This intentionality could allegedly change the history by means of artificial tools avoiding historical and evolutionary processes of the social order in a particular space and time. Moreover, different ends pursued by actors involved could be even antagonistic among them but, as a whole, they could even be producing harmony and benefits to actors involved although the result may differ with respect to different ends individually pursued. To this purpose some of the main works of the following authors are analyzed: Friedrich. A. Hayek, Michael Polanyi, Mantzavinos, North, and Shariq. Conclusions are presented at the end of the article.